On representations of the semigroups S(I,J) with acyclic quiver - Bondarenko, V.M.; Tertychna, O.M. (Інститут математики НАН України, 2009)
In this paper we study representations of semigroups (over a field k) generated by idempotents with partial null multiplication in the case when the corresponding quiver has not oriented cycles.